(untitled) (Research, Society and Development, 2023)
This study deals with the flexibilization of Brazilian labor law, especially regarding the workday of employees submitted to the regime of 12 hours of work for 36 hours of rest. In this context, issues related to the changes brought by Law No. 13,467/2017, the so-called Labor Reform, will be addressed in relation to the aspects of this journey from the perspective of a flexibilization of labor law, its regulation in the legal system and its implications on the health of workers. The study of the theme aims to evaluate potential direct impacts on the rights of workers constitutionally guaranteed, because it is a modality of the working day with broader application, with radiating effects on the social, legal and economic sphere. As a methodological procedure, an applied research is used, from a hypothetical-deductive investigation, with a qualitative approach, developed through a bibliographic, legislative, and jurisprudential review, with the objective of proposing a formative evaluation. It is concluded that the theme is foreseen in the legislation at the same time that it generates controversy due to the unrestricted flexibilization and the worrisome consequences on the worker’s health.